Expression of microRNA‐155 correlates positively with the expression of Toll‐like receptor 7 and modulates hepatitis B virus via C/EBP‐β in hepatocytes. Issue 10 (26th February 2015) - Sarkar, N.; Panigrahi, R.; Pal, A.; Biswas, A.; Singh, S. P.; Kar, S. K.; Bandopadhyay, M.; Das, D.; Saha, D.; Kanda, T.; Sugiyama, M.; Chakrabarti, S.; et al.
Summary Effective recognition of viral infection and successive activation of antiviral innate immune responses are vital for host antiviral defence, which largely depends on multiple regulators, including Toll‐like receptors (TLRs) and microRNAs. Several early reports suggest that specific TLR‐mediated immune responses can control hepatitis B virus (HBV) replication and express differentially with disease outcome. Considering the versatile function of miR‐155 in the TLR‐mediated innate immune response, we aimed to study the association between miR‐155 and TLRs and their subsequent impact on HBV replication using both a HBV‐replicating stable cell line (HepG2.2.15) and HBV‐infected liver biopsy and serum samples. Our results showed that miR‐155 was suppressed during HBV infection and a subsequent positive correlation of miR‐155 with TLR7 activation was noted. Further, ectopic expression of miR‐155 in vitro reduced HBV load as evidenced from reduced viral DNA, mRNA and subsequently reduced level of secreted viral antigens (HBsAg and HBeAg). Our results further suggested that CCAAT/enhancer‐binding protein‐β (C/EBP‐β), a positive regulator of HBV transcription, was inhibited by miR‐155. Taken together, our study established a correlation between miR‐155 and TLR7 during HBV infection and also demonstrated in vitro that increased miR‐155 level could help to reduce HBV viral load by targeting C/EBP‐β.